Statutory Auditors' Independence in Corporate Accounting Scandals: A Case Study of Satyam Computer Services Ltd - Roy, Mitrendu Narayan (Prabandhan: Indian Journal of Management, 2015)
Statutory auditors are professional accountants, external to the business enterprise, appointed to verify authenticity of financial statements of a corporate entity. They accept their responsibility to act in public interest. Thus, auditors play an important role in the economy in protecting stakeholders' interest. In India, Chartered Accountants (CA) perform the significant task of statutory audit of financial statements in Indian companies. Since the financial decision of a large part of the society related to businesses depends upon their opinion, professional institutions like The Institute of Chartered Accountants of India (ICAI) enforce certain regulatory pronouncements to maintain their integrity, independence, and unbiased functioning. These regulatory pronouncements require a statutory auditor to avoid circumstances that may cause threats to their independence. However, if threats are unavoidable, regulation also requires an auditor to apply safeguards available in their work environment or offered by regulation or disciplinary, academic, or non-academic measures. This framework is designed to ensure independence of the statutory auditor in an audit engagement with an ultimate goal of protecting stakeholder interest. In the present day economic environment, greed and tremendous urge to survive in the cut throat competition induces some company managements to breach accounting laws and manipulate their financial statements. Accounting irregularities in the financial statements eventually come under the regulatory radar, leading to a company's demise, thereby impacting most of its stakeholders. Every time a scandal is revealed, a question is raised regarding the auditors' sincerity, integrity, and independence. On many occasions, ensuing investigations into fraud detect an unholy nexus between statutory auditors and managements or their inadvertent negligence that caused disastrous consequences. Among many scandals in different parts of the globe, one notable Indian scandal where independence of the statutory auditor was questioned was the scandal at Satyam Computer Services. In this study, an attempt was made to analyze the extent to which independence of the statutory auditor in the said scandal was impaired and the study also identified possible causes behind it.